Analysis of Decision of The Medan Religious Courts About The Heir that Have Different Religion - Siti Mujihatun S.E., M.M. (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Analysis of Decision of The Medan Religious Courts About The Heir that Have Different Religion